Scientists and the public understanding of science - Pearson, G.; Pringle, S.M.; Thomas, J.N.
This paper discusses the attitudes and opinions of research scientists and engineers to taking part in public understanding of science activities. A survey was carried out at an event in set95 (the UK's 1995 National Week of Science, Engineering and Technology), which involved 168 scientists from the University of Bristol, UK, taking their research work into a shopping mall in Bristol for two days. All participating scientists and engineers were asked to complete a written questionnaire shortly after the event and then at least one participant from each display was contacted seven months later for telephone interview. The results show that while most of the scientists took part because they were told to by senior colleagues, after the event almost all (94 per cent)wanted to take part again mainly because they had found the experience enjoyable. Despite the demands of time and organization, individuals benefited from taking part; participants felt it improved their presentation skills and enhanced morale. They regarded the exhibition as good for communication skills training and did not want formal training for the event. The exhibition was also valued as a team-building exercise both within individual departments and across the University.
Keywords: COMMUNICATION; HISTORY PHILOSOPHY OF SCIENCE